Prevalensi, Karakteristik dan Faktor-faktor yang Berhubungan dengan Penyakit Skabies di Pesantren Nurul Qarnain Kabupaten Jember (The Prevalence, Characteristic and Factors of Scabies in Pesantren Nurul Qarnain Jember) - Ika Rahmawati Sutejo; Viddy Agustian Rosyidi; Alief Ilman Zaelany (Pustaka Kesehatan, 2017)
Scabies is a common skin disease caused by infection of Sarcoptes scabei, which is transmitted directly human-to-human contact especially in crowded community like pesantren. The characteristics of the students in pesantren are seemingly to be associated with Scabies. The purpose of this study was to determine the prevalence, characteristics of Scabies and its association with gender and education level of students in Pesantren Nurul Qarnain Jember. This cross sectional study was conducted to all students (1120 students) in 2016. Diagnosis was made based on anamnesis and dermatology examination. Data were analyzed using chi square test. The results showed that the prevalence of Scabies was 13.48% (male 24.89% and female 5.82%; education level tsanawiyah 15.14.1% and aliyah 10.85%). Most lesions were found in the interdigital space of the hands (40.40%). Chi square test showed significant difference between the prevalence of Scabies with gender (p=0.048) and education level (p=0.023) of the students. In conclusion, the prevalence of Scabies in Pesantren Nurul Qarnain Jember was 13.48% and there was association between the prevalence of Scabies with gender and education level of the students.  Keywords: Scabies, prevalence, students, gender, educational level